2009
DOI: 10.1007/s11538-009-9402-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Proximal Tubule Cell Homeostasis: Tracking Changes in Luminal Flow

Abstract: During normal kidney function, there are are routinely wide swings in proximal tubule fluid flow and proportional changes in Na + reabsorption across tubule epithelial cells. This "glomerulotubular balance" occurs in the absence of any substantial change in cell volume, and is thus a challenge to coordinate luminal membrane solute entry with peritubular membrane solute exit. In this work, linear optimal control theory is applied to generate a configuration of regulated transporters that could achieve this resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 63 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…In all of the steady-state models of the proximal tubule, achieving volume homeostasis in response to increased luminal entry has required activation of peritubular K ϩ -Cl Ϫ and/or Na ϩ -3HCO 3 Ϫ cotransporters, either by volume (51) or by other signals (54); increasing peritubular K ϩ conductance alone was not sufficient. To maintain cell volume homeostasis throughout transient changes in luminal flow, Weinstein and Sontag (52) suggested that a feed-forward signal from the luminal to the peritubular membrane would be required. It was envisioned that this signal would be transmitted by the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In all of the steady-state models of the proximal tubule, achieving volume homeostasis in response to increased luminal entry has required activation of peritubular K ϩ -Cl Ϫ and/or Na ϩ -3HCO 3 Ϫ cotransporters, either by volume (51) or by other signals (54); increasing peritubular K ϩ conductance alone was not sufficient. To maintain cell volume homeostasis throughout transient changes in luminal flow, Weinstein and Sontag (52) suggested that a feed-forward signal from the luminal to the peritubular membrane would be required. It was envisioned that this signal would be transmitted by the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of studies based on control theory [2932], Weinstein identified plausible mechanisms that would allow the proximal tubule cell to adapt to minute-by-minute variations in glomerular filtration without substantial changes in cell volume and composition. Simulations in which transport parameters were varied as a function of cell volume predicted that apical anion exchangers, basolateral Na + -dependent anion exchangers, and basolateral K + channels have very little homeostatic efficiency, whereas modulation of peritubular K + -Cl − and Na+-HCO3- cotransport dampens increases in cell volume without diminishing transcellular Na + transport [30].…”
Section: Introductionmentioning
confidence: 99%
“…Apical microvilli on PT cells have been suggested to function as mechanosensors that transduce changes in FSS to regulate ion transporter trafficking and activity (14). For example, changes in GFR and the accompanying FSS and stretch lead to increases in Na + reabsorption mediated primarily by the insertion of active transporters into the luminal membrane (3, 57). Changes in actin dynamics are thought to play a role in this process; however the exact mechanism for how this leads to altered transporter distribution has not been determined.…”
Section: Introductionmentioning
confidence: 99%